Vegetative Propagation of PeatT Forest Tree Combretocarpus rotundatus (TUMIH (.Miq) Dancer) with Apical Cutting Methods - Istomo Istomo; Rhomi Ardiansyah; Atok Subiakto (Jurnal Silvikultur Tropika, 2012)
Cutting  is  plant  propagation  system which  relatively  easy  and  produces  seeds with good  quality with the similar characteristics as its parent and takes less time. Until now, the success rooted cuttings of tumih still not known certainly. The research aim is determine the effect of giving the hormone IBA 100 ppm, NAA 100 ppm and combination of IBA 50 ppm  and  NAA 50  ppm  on the growth  of  Tumih  shoots  cuttings  (Combretocarpus  rotundatus  (.Miq)  Danser).  The conclusion  that can be  taken on the basis of this research was the addition of plant growth regulators  (IBA, NAA, and IBA + NAA) has no significant effect on the growth of shoots cuttings Tumih (Combretocarpus rotundatus (.Miq) Danser) so  that  the  use  of  growth  regulators  is  not  needed  in  breeding  of  Tumih  shoots  cuttings  (Combretocarpus  rotundatus (. Miq) Danser).